Design of Proving Worksheet Based on APOS Theory on Trigonometric Functions of Sum and Difference of Two Angles - Ardiansyah, Hijir; Hartono, Yusuf; Darmawijoyo, Darmawijoyo (UNNES JOURNAL, 2024)
Trigonometry material is considered difficult by students because there are many formulas and concepts that must be memorized, so students have difficulty in analyzing and describing the problems given. One way for students to understand the formula is by learning proof. In proof learning related to APOS theory to construct students' ability to understand the formula. In this study, a learning media will be made in the form of Worksheet based on APOS theory. The subjects in this study were 11th grade students at SMA Negeri 2 South Kikim. The purpose of this research is to produce a valid, practical, and impactful worksheet theory-based proof worksheet for learning. This study is research and development of a product development type. The development process will be carried out using the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). The data collection techniques used by researchers are interviews, questionnaires, and test questions. The development starts from the initial design of the APOS-based proof worksheet, then validated by three validators. The results of the validation carried out to three experts received a score of 91.85%, so that the worksheet was categorized as very valid and feasible to use. Furthermore, small group trials were carried out, the results obtained a practicality score of 80%, thus the worksheet was categorized as practical. Furthermore, a field test was conducted, to determine the impact of worksheet in learning. The results show that the worksheet has an impact with an effective category with a score of 76.19%. Materi Trigonometri dianggap sulit oleh siswa karena banyak rumus dan konsep yang harus dihafalkan, sehingga siswa kesulitan dalam menganalisi dan menguraikan permasalahan yang diberikan. Salah satu cara agar siswa dapat memahami rumus yaitu dengan pembelajaran pembuktian. Dalam pembelajaran pembuktian berkaiatan dengan teori APOS untuk mengkonstruk kemampuan siswa dalam memahami rumus tersebut. Pada penelitian ini, akan dibuat suatu media pembelajaran berbentuk LKPD pembuktian berbasis teori APOS. Adapun subjek dalam penelitian ini adalah siswa kelas XI di SMA Negeri 2 Kikim Selatan. Tujuan dari penelitian ini adalah untuk menghasilkan LKPD pembuktian berbasis teori APOS yang valid, praktis, serta memiliki dampak terhadap pembelajaran. Jenis penelitian ini adalah penelitian pengembangan tipe pengembangan produk (development study). Proses pengembangan akan dilakukan dengan menggunakan metode ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Teknik pengumpulan data yang digunakan peneliti yaitu wawancara, angket, dan soal tes. Pengembangan dimulai dari mendesain awal LKPD pembuktian berbasis APOS, kemudian divalidasi oleh tiga orang validator. Hasil dari validasi yang dilakukan kepada tiga orang ahli mendapatkan skor sebesar 91,85%, sehingga LKPD dikategorikan sangat valid dan layak digunakan. Selanjutnya dilakukan uji coba kelompok kecil hasilnya mendapatkan skor kepraktisan sebesar 80% Dengan demikian LKPD dikategorikan praktis. Selanjutnya dilakukan field tes, untuk mengetahui dampak LKPD dalam pembelajaran. Hasilnya menunjukan bahwa LKPD memiliki dampak dengan kategori efektif dengan skor 76,19%.